Re-defining the authority in the classroom. Possibilities for a democratic education - José Juan Barba Martín (FEADEF, 2009)
The school always walks behind society. First come the social changes, then changes in the social institutions follow, like in the case of theschools. Years ago, Spain became a democratic society; yet, in its schools, the absolute power of the faculty is still perpetuated. In the following pages,I criticise autocratic authority in the classroom in an attempt to understand what authority is in what ways it manifests itself. Next, I introduce practicalpedagogical suggestions that may help make Physical Education a more democratic subject matter.